Hubungan Minat Ibu dengan Edukasi Stimulasi Tumbuh Kembang Pada Bayi di Klinik Bidan Wanti Medan - Pipit Kurniasari; Restika Wulandari; Reza Bunga Uli Br. Manurung; Ria Juliana; Rina Rina (Universitas Malahayati Lampung, 2025)
ABSTRACT This study aims to analyze the relationship between mothers' interest and early childhood stimulation education for infants at Bidan Wanti Clinic in Medan. The background of this research is related to the low participation of mothers in providing stimulation for child development, despite receiving related education. This study uses an analytical quantitative research design with a cross-sectional approach. The sample used in this study consisted of 30 mothers with infants aged 0-24 months, selected using purposive sampling technique. Data was collected through a questionnaire measuring the mothers' interest in child development stimulation and the level of education they received. Data analysis was performed using Pearson's correlation test to determine the relationship between the two variables. The results showed a significant relationship between mothers' interest and stimulation education (p-value = 0.004), where mothers with higher interest were more likely to actively engage in receiving the education. These findings highlight the importance of increasing mothers' interest in early childhood stimulation education to optimize infant development. This study is expected to serve as a reference for improving the quality of early childhood stimulation education programs in the future. Keywords: Maternal Interest, Stimulation Education, Infant Development. ABSTRAK Penelitian ini bertujuan untuk menganalisis hubungan antara minat ibu dengan edukasi stimulasi tumbuh kembang pada bayi di Klinik Bidan Wanti Medan. Latar belakang penelitian ini berkaitan dengan rendahnya partisipasi ibu dalam memberikan stimulasi tumbuh kembang meskipun telah menerima edukasi terkait. Penelitian ini menggunakan desain penelitian kuantitatif analitik dengan pendekatan cross-sectional. Sampel yang digunakan dalam penelitian ini berjumlah 30 ibu yang memiliki bayi usia 0-24 bulan, yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui kuesioner yang mengukur minat ibu terhadap stimulasi tumbuh kembang dan tingkat edukasi yang diterima ibu. Analisis data dilakukan dengan uji korelasi Pearson untuk mengetahui hubungan antara kedua variabel. Hasil penelitian menunjukkan adanya hubungan yang signifikan antara minat ibu dengan edukasi stimulasi tumbuh kembang (p-value = 0,004), di mana ibu dengan minat tinggi cenderung lebih aktif menerima edukasi tersebut. Temuan ini menunjukkan pentingnya meningkatkan minat ibu dalam edukasi stimulasi tumbuh kembang agar dapat memaksimalkan perkembangan bayi. Penelitian ini diharapkan dapat menjadi referensi bagi peningkatan kualitas program edukasi stimulasi tumbuh kembang di masa mendatang. Kata Kunci: Minat Ibu, Edukasi Stimulasi, Tumbuh Kembang Bayi.